2019
DOI: 10.4236/jsbs.2019.93007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Biogas Production from Cow Dung as an Alternative for Fossil Fuels

Abstract: To treat the problem of fossil fuel usage and greenhouse gas emissions, biogas is considered a potential source of clean renewable energy. The aim of the work is to analyze the amount of biogas and ph from cow dung when an anaerobic digester operates in the mesophilic mode. In this study is presented the experimental investigation of biogas production from cow dung as an alternative energy resource. This is work using an 18 Liters capacity plastic as prototype biogas plant, plant to inspect the anaerobic diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Esta tecnología es clave en la disminución de emisiones de metano (CH4), un potente gas de efecto invernadero, que se libera durante la descomposición natural del estiércol (Solano, 2019;Alvarado, De Oliveira, De Oliveira, Damasceno, y Alvez, 2020;Ngo, Ball, y Shahsavari, 2021). Además, la DA facilita la producción de biogás, reconocido como una fuente de energía renovable y sostenible, que contribuye significativamente a la reducción de gases de efecto invernadero al reemplazar combustibles fósiles en la generación de calor y electricidad (Benali, Hamad, y Hamad, 2019;Solano, 2019;Alvarado et al, 2020;Ngo et al, 2021;Sanaye y Yazdani, 2022). Según Ngo et al (2021), el tratamiento de una tonelada de desechos mediante la DA puede resultar en una disminución de 0.143 toneladas de equivalente de CO2.…”
Section: ¿Cómo Convertir Un Gei En Energía Limpia En La Actividad Pec...unclassified
“…Esta tecnología es clave en la disminución de emisiones de metano (CH4), un potente gas de efecto invernadero, que se libera durante la descomposición natural del estiércol (Solano, 2019;Alvarado, De Oliveira, De Oliveira, Damasceno, y Alvez, 2020;Ngo, Ball, y Shahsavari, 2021). Además, la DA facilita la producción de biogás, reconocido como una fuente de energía renovable y sostenible, que contribuye significativamente a la reducción de gases de efecto invernadero al reemplazar combustibles fósiles en la generación de calor y electricidad (Benali, Hamad, y Hamad, 2019;Solano, 2019;Alvarado et al, 2020;Ngo et al, 2021;Sanaye y Yazdani, 2022). Según Ngo et al (2021), el tratamiento de una tonelada de desechos mediante la DA puede resultar en una disminución de 0.143 toneladas de equivalente de CO2.…”
Section: ¿Cómo Convertir Un Gei En Energía Limpia En La Actividad Pec...unclassified
“…Fossil fuels are the main source of energy on the planet (Benali, Hamad, and Hamad, 2019). This kind of energy source releases a significant amount of carbon dioxide gas, one of the main greenhouse gas contributors.…”
Section: Introductionmentioning
confidence: 99%
“…Cunsheng et al [19] reported that codigestion of cattle manure with food waste in batch mode at an optimal ratio of 2:1 (manure: food waste) increased methane production by 41%, from 2624 ml to 3725 ml, compared to mono-digestion. Benali et al [20] Effect of solid concentrations on anaerobic digestion of cow manure. This research aims to determine the optimum water dilution which will produce a high biogas yield.…”
Section: Introductionmentioning
confidence: 99%